Utility of right adrenal signature veins in venous sampling for primary aldosteronism - Zhenglin Shen; Shaoyong Xu; Siyu Guan; Bo Chen; Qingan Li; Ming Yu; Zhao Gao (Annals of Medicine, 2023)
AbstractBackground This study aimed to identify the appropriate signature veins for the right adrenal gland using a 3D model fused with adrenal venography images and to verify their accuracy through the selectivity index (SI) >2.Methods We analyzed the right adrenal venography images of 41 patients who underwent adrenal venous sampling (AVS). These images were merged with a 3D structure of the adrenal gland to identify the signature veins of the right adrenal gland. We then used the signature veins observed during adrenal venography to determine the optimal position of the catheter tip during AVS for 53 other patients. Finally, we verified the accuracy of this method according to the SI.Results We successfully fused the 3D models of 41 cases with adrenal venography images. We identified the trunk branch type as the major venous morphology in the right anterior oblique at degrees of 30 (38 cases, 92.7%). In addition, the central vein, brush vein, uvula vein, and capsular vein were identified as signature veins for the right AVS. The accuracy of AVS was 100% in the other 53 patients, as verified by an SI >2.Conclusions Our study identified the right adrenal signature veins, including the previously overlooked uvula vein, which can be used to determine the position of the catheter tip and improve the success rate of AVS.